Hypoxia and lactate influence VOC production in A549 lung cancer cells - Furuhashi, Takeshi; Matsumoto, Yuki; Ishii, Ryuga; Sugasawa, Takehito; Ota, Shigenori (Frontiers in Molecular Biosciences, 2023)
Introduction: Cancer cells emit characteristic volatile organic compounds (VOCs), which are potentially generated from ROS-based lipid peroxidation of polyunsaturated fatty acids. The metabolism of such VOCs and their regulation remain to be fully investigated. In fact, the enzymes involved in the synthesis of these VOCs have not been described yet. Methods: In this study, we firstly conducted in vitro enzyme assays and demonstrated that recombinant alcohol dehydrogenase (ADH) converted Trans 2-hexenal into Trans 2-hexenol. The latter has previously been reported as a cancer VOC. To study VOC metabolism, 14 different culture conditions were compared in view of Trans 2-hexenol production. Results and discussion: The data indicate that hypoxia and the addition of lactate positively influenced Trans 2-hexenol production in A549 cancer cells. The RNAseq data suggested certain gene expressions in the VOC pathway and in lactate signaling, parallel to VOC production. This implies that hypoxia and lactate signaling with a VOC production can be characteristic for cancer in vitro.